Safety riding training for youth oil palm transporter in Persiapan Ranah Melintang village, West Pasaman district - M. Yasep Setiawan; Nuzul Hidayat; Ahmad Arif; Wawan Purwanto; Martias Martias; Dwi Sudarno Putra (Universitas Muhammadiyah Magelang, 2023)
Of 120 work accidents and work-related body injury reports, 75% occurred in young transporters. These are caused by young oil palm transporters' lack of understanding and ability to drive safely, especially in oil palm plantation sites with uneven road characteristics, and the vehicle specifications need to be safer to drive. This community service aims to provide knowledge and skills to the people of Persipan Ranah Melintang village, especially young oil palm transporters, regarding driving safety so that it can reduce the number of accidents in this area. The method used in the safety riding training activities uses the lecture method, question and answer, discussion, video demonstrations, and sound and proper practice of riding a motorbike following safety riding rules. The results of this activity showed the participants' enthusiasm for participating in the training, especially when practicing riding motorbikes. In addition, there was an increase in participants' awareness and understanding of the importance of safety riding when driving.